Analysis of Surgical Resident Operative Volumes on China's Resident Training. (October 2020) - Liu, Wei; Han, Xiaoling; Zhou, Xu; Zhou, Chongzhi; Wang, Min
Doctors entering surgical residency with different educational degrees and from different specialties is a unique feature of the Chinese medical system. The effect of this on the experience of surgical residents is not known. We retrospectively investigated whether residents' operative volumes were based on highest educational degree or postgraduate specialty. Using our operating data management system, a retrospective analysis of surgical resident operative experience at Shanghai General Hospital from 2012 to 2017 was conducted. The overall monthly average operative volume for surgical residents was 17.7 (12.6-26.5), but this decreased with each advanced degree of education from 26.0 (19.2-34.5) for those with a bachelor's degree only, to 19.5 (16.0-28.1) for a master's degree, to 15.9 (12.2-22.9) for those with a doctorate. Regarding specialty, residents in plastic surgery had the highest operative volume, and those in cardiothoracic surgery and neurosurgery had the lowest. At Shanghai General Hospital, the operative volumes of surgical residents differed according to their highest educational degree and postgraduate specialty. This analysis should be useful for the future planning of surgical residency programs in China.